Carboxylated Graphene for Radical-Assisted Ultra-Trace-Level Water Treatment and Noble Metal Recovery - Kolařík, Jan; Bakandritsos, Aristides; Bad'ura, Zdeněk; Lo, Rabindranath; Zoppellaro, Giorgio; Kment, Štěpán; Naldoni, Alberto; Zhang, Yu; Petr, Martin; Tomanec, Ondřej; Filip, Jan; Otyepka, Michal; et al. (ACS nano, 2021)
Sorption technologies, enabling removal of heavy metals, play a pivotal role in meeting the global demands for unrestricted access to drinking water. Standard sorption technologies suffer from limited efficiency related to the weak sorbent-metal interaction. Further challenges include the development of technologies enabling smart metal recovery and sorbent regeneration. To this end, a densely functionalized graphene, with 33% by mass content of carboxyl groups, linked through direct C-C bonds (graphene acid, GA) represents a previously unexplored solution to this challenge. GA revealed excellent efficiency for removal of highly toxic metals, such as Cd2+ and Pb2+. Due to its selective chemistry, GA can bind heavy metals with high affinity, even at concentrations of 1 mg L-1 and in the presence of competing ions of natural drinking water, and reduce them down to drinking water allowance levels of a few μg L-1. This is not only due to carboxyl groups but also due to the stable radical centers of the GA structure, enabling metal ion-radical interactions, as proved by EPR, XPS, and density functional theory calculations. GA offers full structural integrity during the highly acidic and basic treatment, which is exploited for noble metal recovery (Ga3+, In3+, Pd2+) and sorbent regeneration. Owing to these attributes, GA represents a fully reusable metal sorbent, applicable also in electrochemical energy technologies, as illustrated with a GA/Pt catalyst derived from Pt4+-contaminated water.
Keywords: metals; adsorption; recovery; water treatment; electrocatalysis